Zooplankton of two shallow lakes in the south of Meauco formation (la Pampa Province, Argentina) (Semiárida, 2020)
The Meauco Formation, a dune region of the central Pampa province, has numerous shallow lakes. Although there is hydrological information about them, it is very scarce about their limnological characteristics. The objectives are to know the physical-chemical and zooplankton parameters of two nearby shallow lakes, with and without fishes: Santa Isabel I (SI I) and Santa Isabel II (I II) respectively, and determine the influence of zooplankton on phytoplankton biomass and transparency. It was sampled during 2018 and 2019. In both the mean salinity were less than 1g.L-1 and the Secchi disk depth was around 0.45m. The chlorophyll concentrations varied between 9.32 and 11.63 mg.m-3. Seven cladocerans, 4 copepods and 20 rotifers were recorded. Most of the taxa were shared by both lakes, however, 20 rotifers were recorded in SI I and 13 in SI II. The total zooplankton density did not differ, but SI I had greater abundance of rotifers (69% of total) and SI II of crustaceans (72%). The presence of fish influences the zooplankton composition but its small size, even in the absence of fish, makes it have little influence on the phytoplankton; therefore, no differences were found in the transparency and phytoplankton biomass of both lakes.
Keywords: Subsaline shallow lakes; zooplankton; chlorophyll-a; Odontesthes bonariensis